Image compression–encryption scheme based on hyper-chaotic system and 2D compressive sensing. (August 2016) - Zhou, Nanrun; Pan, Shumin; Cheng, Shan; Zhou, Zhihong
Abstract: Most image encryption algorithms based on low-dimensional chaos systems bear security risks and suffer encryption data expansion when adopting nonlinear transformation directly. To overcome these weaknesses and reduce the possible transmission burden, an efficient image compression–encryption scheme based on hyper-chaotic system and 2D compressive sensing is proposed. The original image is measured by the measurement matrices in two directions to achieve compression and encryption simultaneously, and then the resulting image is re-encrypted by the cycle shift operation controlled by a hyper-chaotic system. Cycle shift operation can change the values of the pixels efficiently. The proposed cryptosystem decreases the volume of data to be transmitted and simplifies the keys distribution simultaneously as a nonlinear encryption system. Simulation results verify the validity and the reliability of the proposed algorithm with acceptable compression and security performance. Abstract : Highlights: A simultaneous image encryption–compression scheme based on 2D CS and hyperchaos is proposed. The nonlinear cycle shift operation controlled by a hyper-chaotic system is used for diffusion. The hyper-chaotic system with good randomness and sensitiveness is used to generate random sequences. The data of the ciphertext is decreased and the security is improved due to double encryptions.